2017
DOI: 10.1038/oncsis.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of zinc finger protein 687 enhances tumorigenic capability and promotes recurrence of hepatocellular carcinoma

Abstract: Zinc finger protein 687 (ZNF687), identified as a C2H2 zinc finger protein, has been found to be mutated and upregulated in giant cell tumor of bone and acute myeloid leukemia, suggesting an oncogenic role for ZNF687 in cancer. However, the clinical significance and precise role of ZNF687 in cancer progression are largely unknown. Herein, we report that ZNF687 was markedly upregulated in hepatocellular carcinoma (HCC) cell lines and HCC tissues, and was significantly correlated with relapse-free survival in HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…ZFPs represent the largest and most diverse family of DNA binding transcription factors as they can bind to DNA, RNA, and other proteins with high specificity. ZnTs, ZIPs, and ZFPs have demonstrated relevance in important aspects of health ranging from epigenetic changes via DNA methylation [14,15] to development [15][16][17][18], cancer progression/repression [19][20][21][22][23][24][25][26][27], bone remodeling/mineralization, and atherosclerosis.…”
Section: Physiological Role Of Znmentioning
confidence: 99%
“…ZFPs represent the largest and most diverse family of DNA binding transcription factors as they can bind to DNA, RNA, and other proteins with high specificity. ZnTs, ZIPs, and ZFPs have demonstrated relevance in important aspects of health ranging from epigenetic changes via DNA methylation [14,15] to development [15][16][17][18], cancer progression/repression [19][20][21][22][23][24][25][26][27], bone remodeling/mineralization, and atherosclerosis.…”
Section: Physiological Role Of Znmentioning
confidence: 99%
“…Several forkhead box proteins (14) and zinc finger proteins (ZNFs) (1521) have also been reported to serve crucial roles in HCC. Recently, a study demonstrated that ZNF687 overexpression promotes HCC recurrence (22); however, the TFs associated with HCC relapse remain unknown (22).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jen et al 20 identified C2H2-type zinc finger protein ZNF322A as a transcriptional inhibitor of c-Myc, thus maintaining lung cancer stem cell-like properties by altering metabolism towards oxidative phosphorylation. Zhang et al 21 found that ZNF687 with C2H2 domain could enhance tumor development and promotes recurrence of hepatocellular carcinoma through transcriptional regulating BMI1, OCT4, and NANOG. On the other hand, although ZNF280A contains two consecutive C2H2-type zinc finger domain transcription factors, there are few studies on its tumor biology.…”
Section: Discussionmentioning
confidence: 99%